Neuroeconomics: decisions in extreme situations - Chavaglia, J. N.; Filipe, J. A.; Ferreira, M. A. M.; Caleiro, A. (EC Business Management, 2015)
The role of the electorate has been confirmed as fundamental to the development of democratic countries. However, governments and large corporations have increasingly intervened in the decision-making capacity of the voters who are now seen as “customers”. This is the starting point for this article that will discuss the power of external influence in the decision-making process of the act the polling day and the importance of the context effect in the decision-making process of individuals.